2020
DOI: 10.23955/rkl.v15i2.17618
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Activated Carbon Made from Robusta Coffee Skin (Coffea Canephora)

Abstract: Indonesia is one of the coffee-producing countries where production tends to increase from year to year. Currently, residuals from coffee-fruit processing such as coffee-skin and husks are thrown away without any use and this biomass residual contains several toxic chemicals such as alkaloids, tannins, and polyphenols. One of potential uses of coffee-industry by-product is to make activated carbon (ACs), which is made through a carbonation process and followed by an activation process. In this study, chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although in this study, the nitrogen absorption test at low pressure was more supportive of the desorption value. The highest surface area value was shown by the coffee pulp sample pyrolyzed at a temperature of 400 o C. An increase in this pyrolysis temperature to 500 o C reduces the surface area of the sample and the formation of carbon with surface pores due to high temperatures which burn raw materials (Raihan;Setiawan;Hakim, 2020).…”
Section: Bet Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although in this study, the nitrogen absorption test at low pressure was more supportive of the desorption value. The highest surface area value was shown by the coffee pulp sample pyrolyzed at a temperature of 400 o C. An increase in this pyrolysis temperature to 500 o C reduces the surface area of the sample and the formation of carbon with surface pores due to high temperatures which burn raw materials (Raihan;Setiawan;Hakim, 2020).…”
Section: Bet Analysis Resultsmentioning
confidence: 99%
“…It was cleaned of dirt and dried under the sun until it reached a moisture content of 5% to 10%. Afterward, the CP weighed three kg and was placed in the pyrolysis reactor for the carbonization process (Raihan;Setiawan;Hakim, 2020). CP Heating was carried out in the reactor at 400 ºC and 500 ºC for 3 hours and cooled to room temperature.…”
Section: Coffee Pulp Preparation and Carbonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the bio-char produced from coffee pulp has ash content of 15.8% which is still quite high. According to the Indonesian National Standardization Agency (BNSI), the maximum ash content is 10% and the maximum moisture content is 15% (9). As reported earlier (10), washing is one of effective methods to be used to remove ash content or other minerals from biomass.…”
Section: Introductionmentioning
confidence: 98%
“…To overcome this problem, biomass needs to be processed further by improving the quality of production of energy conversion materials. Thermochemical conversion of energy from biomass consists of pyrolysis technology [6]- [9], gasification [10]- [12], torefaction [13]- [16], Hydrothermal carbonization [17]- [20], and direct combustion [21]- [24].…”
Section: Introductionmentioning
confidence: 99%